Financial Inclusion in Nepal: Policy Review and Prescriptions - Pant, Bhubanesh (NRB Economic Review, 2016)
With financial inclusion playing a vital role in reducing poverty and income disparity, it is emerging as a top priority for policymakers and regulators. A large number of countries have introduced comprehensive measures to improve access to and usage of tailored financial services. Greater financial inclusion is achieved when all economic activities and segments of the society have access to financial services with ease and at minimum cost. In the case of Nepal, though the need for financial inclusion by encompassing more and more of the excluded population by the formal financial system has been regularly emphasized in the country’s policy framework, a large section of population still remains outside the formal financial system. This paper, after assessing some relevant data on financial inclusion, reviews the policy measures implemented for enhancing it. The majority of the measures could not be executed to the degree desired due to problems of low financial literacy, paucity of infrastructural facilities as well as inadequate technology-based facilities, among others. Against this perspective, this study seeks to provide some prescriptions for enhancing financial inclusion in the country. These include, among others, promotion of financial literacy programs, launching of digital financial services, formulation of National Financial Inclusion Strategy, implementation of a Financial Inclusion Roadmap and according special role to microfinance institutions.